The clinical characteristics and microbiological investigation of pediatric burn patients with wound infections in a tertiary hospital in Ningbo, China: A ten-year retrospective study - Ke, Yefang; Ye, Lina; Zhu, Pan; Zhu, Zhe (Frontiers in Microbiology, 2023)
Burn is one of the leading causes of death and disability in children worldwide, and wound infection is an excellent challenge in burn treatment. We performed a retrospective review of pediatric burn patients with wound infections to reveal their clinical data and investigate pathogens' distribution and drug resistance patterns to provide references for treatment. As a result, 330 pediatric burn patients with wound infections were identified; 65.8% (217/330) were <2 years old. Most of the injuries were scalded and involved <10% total body surface area in size (TBSA), mainly causing Ⅱ-degree burn and Ⅱ+Ⅲ-degree burn. 359 strains of pathogens were isolated, the primary pathogens were Staphylococcus aureus (45.4%) and Pseudomonas aeruginosa (18.7%). Both Staphylococcus aureus and Pseudomonas aeruginosa isolated from 2012-2016 were more likely to be multi-resistant than those isolated from 2017-2021, as they were significantly associated with resistance to ≥ 4 Clinical and Laboratory Standard Institute (CLSI) classes (P=0.040 and 0.006, respectively). In conclusion, children aged <2 years old were the main pediatric burn patients with wound infections. The primary bacteria isolated from the wound were Staphylococcus aureus and Pseudomonas aeruginosa, with a decreasing tendency of multi-resistance.